Validitas Awal instrumen European Quality of Life (EQ-5D-5L) versi Indonesia pada kualitas hidup penderita hepatitis B - Hasniah Hasniah; Dyah Ariani Perwitasari; Woro Supadmi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Health-related quality of life (HRQoL) is an important aspect in the management of chronic diseases such as hepatitis B, considering the long disease course and the risk of complications including cirrhosis and hepatocellular carcinoma. The European Quality of Life instrument (EQ-5D-5L) is widely used globally to assess quality of life; however, psychometric evidence in patients with hepatitis B in Indonesia remains limited. This study aimed to evaluate the preliminary validity and reliability of the Indonesian version of the EQ-5D-5L among patients with hepatitis B in primary healthcare settings. This study employed an observational design with a cross-sectional approach involving 42 female patients with confirmed HBsAg positivity who participated in a hepatitis B early detection program at primary health centers in Banjarmasin City between April and October 2025. Data were collected using the EQ-5D-5L questionnaire, the EQ visual analogue scale (EQ-VAS), and a demographic characteristics form. Reliability was assessed using Cronbach’s alpha, while construct validity was evaluated using item–total correlation with a significance threshold of r-table = 0.304. Statistical analyses were performed using SPSS version 26. The results indicated that the EQ-5D-5L questionnaire demonstrated good internal consistency with a Cronbach’s alpha value of 0.799. All items showed item–total correlations greater than the r-table value (0.304), indicating that all domains were valid. Correlation analysis revealed a significant relationship between EQ-VAS scores and the EQ-5D-5L utility index (r = 0.669; p < 0.001), suggesting adequate construct validity. Within the limitations of this study, the Indonesian version of the EQ-5D-5L demonstrates potential as a tool for measuring quality of life among female patients with hepatitis B in primary healthcare settings.